ダイ16ジ ナンキョク チイキ カンソク カイヒョウ ホウコク リュツオ ホルムワン フキン ノ ヒョウジョウ 1974ネン 12ガツ 1975ネン 2ガツ - 滝沢, 隆俊; タキザワ, タカトシ; TAKIZAWA, Takatoshi (国立極地研究所, 1976)
P(論文) On December 25, 1974, icebreaker FUJI of the 16th Japanese Antarctic Research Expedition reached the ice edge at 63°06'S, 83°03'E, and on February 21, 1975 she left the ice off the Riiser-Larsen Peninsula at 67°41'S, 34°15'E. Visual ice observations aboard the ship were carried out every four hours, excluding the period from January 5 to February 11, 1975. An ice chart was compiled from shipboard observations supplemented with helicopter observations. Offshore regions of the Prince Olav Coast and Lutzow-Holm Bay were covered with very close pack ice in which medium or small floes were predominant. The ice thickness was generally less than 1.5m. However, there were some thick floes, several meters thick, which consisted of two or three layers. They are obviously a result of piling up of ice sheets. At the beginning of January a series of flaw polynias was found between 40.5°E and 43°E, about 25 nautical miles from the shore of the Prince Olav Coast. On February 12, 1975, the FUJI on her return voyage was beset by ice at 69°10'S, 38°56'E and drifted westward for about a week; consolidated floes with pressure ridges of 1 m to 3 m high surrounded the ship. The average drifting speed was about 0.2 knot. departmental bulletin paper